Is There Any Match Between Students’learning Style, Strategies, And Lecturers’ Teaching Techniques ? A Case Study of Benin EFL Students at the University Level - Hounhanou, Arlette Joséline Viviane (My University, 2018)
Educational research has identified a number of factors for some of the differences in how students learn (Reid, 1987). One of these factors, learning styles, is of widespread interest in the education area. In fact, each of us has an individual learning style, which means that we learn and process information in different ways. Also, there has been a prominent shift within the field of learning strategies, and teaching techniques over the last twenty years. How students process new information and what kinds of strategies they employ to understand, learn or remember the information has been the primary concern of number of researchers. Furthermore, the way courses are delivered by lecturers, the teaching techniques used has a great impact on students’ achievement. The objective of this current study aims at establishing a comparison between two groups of students at the university level. (A Training College and a Public University) in order to determine their learning preference, strategies, and the teaching techniques that they would best select. The researcher collected data from a sample of approximately 225 students. From the data, there is a significant difference between the two types of students in terms of the appropriate teaching, techniques used by lecturers and their match with students’ learning style and strategies.
Keywords: Learning Style; Strategies; Students; Teaching Techniques